A model of optimal labour and soil use with shifting cultivation - Unai Pascual; Edward Barbier (Fondazione Eni Enrico Mattei (FEEM), 2001)
This paper analyses the relationship between rural poverty and soil degradation in the context of a shifting cultivating community. A deterministic optimal control model demonstrates how a representative household's labour allocation affects the natural resource base on which its livelihood largely depends. The comparative static examination of relevant parameters and welfare effects of changes in the real wage rate are discussed. The theoretical results obtained are calibrated with data from the Yucatán, México.
Keywords: Q12; Q23; D13; I3; 330; Bodenbelastung; Ländliche Armut; Haushaltsökonomik; Landwirtschaftliche Bodennutzung; Bioökonomik; Theorie; Yucatán